KNOWLEDGE-BASED VARIABLES IN THE SUSTAINABILITY OF PRIVATE UNIVERSITIES IN EAST JAVA - 1 (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2021)
Organisational sustainability is closely linked to the organisation's brand image in the eyes of stakeholders and the wider community. Each organisation can build a positive image through effective communication or innovative marketing models, one of which is social media. Social media is the most appropriate means of communication and marketing for universities to recruit prospective students. This study analysed the role of knowledge-based variables in building higher education sustainability, as universities are knowledge institutions and always maintain or develop knowledge through research activities. Knowledge-based variables include Intellectual Capital, University Management Intelligence, and Social Media. Based on this, this research aimed to find out the significance of knowledge-based variables in the sustainability of private universities in East Java. This research focused on human behaviour by using a survey with a quantitative approach and data collected through a questionnaire. This study concludes that Social Media Marketing does not reduce the impact of intellectual capital on private universities' sustainability in East Java. Social Media Marketing does not reduce the impact of the University Managerial Intelligence on the sustainability of private universities in East Java.